2018
DOI: 10.1002/ejlt.201800177
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of Pomegranate Seed Oil: A Promising Approach of Improving Stability and Health‐Promoting Properties

Abstract: Emerging evidence has suggested that nutraceutical ingredients like pomegranate seed oil (PSO) possesses health‐promoting effects in cell and animal models. However, these health benefits (anticancer, antioxidant, anti‐inflammatory, anti‐diabetic, and so on) are limited by low physicochemical stability, slow intestinal absorption, and rapid metabolism of PSO. In order to overcome these drawbacks, some carriers viz., nanoemulsion, encapsulation, and nanoparticles are developed recently. This paper assesses the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 113 publications
0
7
0
Order By: Relevance
“…Application of punicic acid in therapy however poses some questions: it is slowly absorbed and it is rapidly metabolized forming other conjugated isomeric linolenic fatty acids such as catalpic and αand β-eleostearic acids. Alternatively, the use of appropriate formulations of pomegranate seed oil such as encapsulation into lipid-based carrier systems, nanoemulsion delivery systems or nanodispersions is being considered to protect the active fatty acids from degradation (Adu-Frimpong et al 2018).…”
Section: Punicic and Catalpic Acidsmentioning
confidence: 99%
“…Application of punicic acid in therapy however poses some questions: it is slowly absorbed and it is rapidly metabolized forming other conjugated isomeric linolenic fatty acids such as catalpic and αand β-eleostearic acids. Alternatively, the use of appropriate formulations of pomegranate seed oil such as encapsulation into lipid-based carrier systems, nanoemulsion delivery systems or nanodispersions is being considered to protect the active fatty acids from degradation (Adu-Frimpong et al 2018).…”
Section: Punicic and Catalpic Acidsmentioning
confidence: 99%
“…The fruit known as pomegranate ( Punica granatum ) originated from the Middle East, then extended to Mediterranean areas, as well as in countries such as Iran, India, China, Japan, and Russia. Pomegranate has been used as a traditional medicine in Asian cultures to treat different ailments (Adu‐frimpong et al., 2018 ). Many epidemiological studies of the potential effects of pomegranate on cancer prevention, such as lung cancer (Khan et al, 2007 ), skin cancer (Rout & Banerjee, 2007 ), prostate cancer (Malik et al., 2005 ), breast cancer (Toi et al, 2003), etc.…”
Section: Typical Superfruits In China and Their Potential Health Benefitsmentioning
confidence: 99%
“…In addition, emerging evidence has suggested that nutraceutical ingredients like PSO possessed health‐promoting effects in cell and animal models. However, these health benefits (anticancer, antioxidant, anti‐inflammatory, anti‐diabetic, and so on) are limited by low physicochemical stability, slow intestinal absorption, and rapid metabolism of PSO (Adu‐frimpong et al., 2018 ).…”
Section: Typical Superfruits In China and Their Potential Health Benefitsmentioning
confidence: 99%
“…Previous work suggested that cuminaldehyde could improve the activity of liver enzymes in vitro , but, its in‐vivo antihepatotoxicity has not been reported yet. Like other natural essential oils (EOs), the use of free cuminaldehyde usually leads to decreased bioactivity because of low bioavailability caused by volatilisation, hydrophobicity and rapid enzymatic metabolisation . Cuminaldehyde could therefore be formulated via appropriate novel techniques to enhance its oral bioavailability and therapeutic efficacy as other natural bioactive compounds .…”
Section: Introductionmentioning
confidence: 99%
“…Like other natural essential oils (EOs), the use of free cuminaldehyde usually leads to decreased bioactivity because of low bioavailability caused by volatilisation, hydrophobicity and rapid enzymatic metabolisation. [24,25] Cuminaldehyde could therefore be formulated via appropriate novel techniques to enhance its oral bioavailability and therapeutic efficacy as other natural bioactive compounds. [20,25,26] Several reports indicated that carriers such as liposomes, cyclodextrin inclusion complexes and drugin-cyclodextrin-in-liposome systems have been used to encapsulate various EOs and their components, viz.…”
Section: Introductionmentioning
confidence: 99%